Risk Factors of Benign Stricture of Anastomotic Stoma after Esophagectomy and Therapeutic Effect of Stent Implantation - Guoliang Wu; Lihua Niu; Yanlin Yang; Shaoyong Tian; Yanru Liu; Chunyan Wang; Pengfei Zhao (Emergency Medicine International)
With the increase in the number of patients and prolongation of their lives after esophagectomy for esophageal cancer, the quality of life after surgery has attracted more and more attention. Although anastomotic stenosis is a common complication, it seriously affects the quality of life and psychological state of patients or even threatens their lives. At present, the exact independent influencing factors of anastomotic stenosis after esophageal cancer surgery have not been determined, and relevant treatment options are still controversial. Here, we analyzed the independent risk factors leading to good postoperative anastomotic stenosis, in order to provide a basis for late prevention. At the same time, we deeply discussed the advantages and safety of stent implantation in the treatment of anastomotic stenosis.